Bibliometric review on geopolymer modified with nanomaterialusing VOS viewer - Al-Baldawi, Maryam Firas; Abdul Aziz, Farah Nora Aznieta; Abbas, Al Ghazali Noor; Mohd Nasir, Noor Azline; Abdan, Khalina; Mohamed Sutan, Norsuzailina (Universiti Putra Malaysia Press, 2025)
Geopolymer composites modified with nanomaterials have gained significant interest in recent years due to their improved properties. The nanoparticles can form extra C-S-H gel, reducing porosity and generating a denser microstructure. Manual reviews cannot effectively manage the immense bibliometric data. Therefore, this manuscript reviews nanomaterials in geopolymer by adopting a scientometric evaluation as a form of analysis via visualization of similarities software in the VOS viewer. A bibliometric network is created and depicted to analyze the annual distribution and growth pattern, prominent sources, frequent keywords, top articles, and leading countries of geopolymer modified with nanomaterials via the searched words in the Scopus database of “geopolymer” and “nanomaterial” that successfully achieved 529 documents from 2008 to October 2023. The results of the scientometric study indicate that Construction and Building Materials appears as the top publication source, in terms of article amount and citation count, and the most frequently utilized keywords in these publications are nanomaterial, geopolymers, and inorganic polymers. Furthermore, the countries that have demonstrated the highest levels of activity and contribution in terms of publications are China, India, and the United States. The inclusion of participating nations and researchers is facilitated through quantitative and graphical representations. This review has the potential to provide valuable insights to academics in the field of forming collaborations and discussing novel ideas and methods. This is mostly due to the inclusion of visual and statistical depictions that showcase the participating nations and authors of the study.